Dazzle's First Day - Moss, Olivia; Illustrated by Chaffey, Sam (London Scholastic, 2008)
Dazzle is a brand-new butterfly, fresh out of her cocoon. She doesn't know how to fly, and she's all alone! But Butterfly Meadow could be just what Dazzle is looking for.
Including Illustrations
Keywords: Butterflies